Nebivolol: A Different Beta-Blocker for Hypertension - Otljanska, M; Kostova, Nela; Boshev M; Otljanski, A (MedCrave, 2016)
Beta blockers are one of the classes of antihypertensive drugs, but there are controversies of their use as an initial therapy in treatment of arterial hypertension based on different guidelines for treatment of arterial hypertension. Nebivolol is a third generation, highly selective β-adrenoceptor antagonist with antihypertensive efficacy similar to other beta blockers but with unique function of increasing the release of nitric oxide (NO) via activation of β3-adrenergic receptors which improves endothelial function, produces vasodilatation, improves arterial compliance and reduces peripheral vascular resistance. Nebivolol highly selective lipophilic B1-adrenergic receptor antagonist and B3 agonist has different pharmacokinetics and pharmacodynamics profile from other beta blockers with more favourable metabolic and hemodynamic profile, like side effect profile, beta receptors blockade affinity, vasodilating properties, and improvement of endothelial function. Nebivolol has been show to be effective beta blocker for treatment of mild to moderate arterial hypertension as monotherapy or in combination therapy.
Keywords: beta blockers; nebivolol; endothelial function; nitric oxide